Hydroxyurea treatment inhibits proliferation of Cryptococcus neoformans in mice - Tripathi, Kaushlendra; Mor, Visesato; Bairwa, Narendra K.; Del Poeta, Maurizio; Mohanty, Bidyut K. (Frontiers in Microbiology, 2012)
The fungal pathogen Cryptococcus neoformans (Cn) is a serious threat to immunocompromised individuals, especially for HIV patients who develop meningoencephalitis. For effective cryptococcal treatment, novel antifungal drugs or innovative combination therapies are needed. Recently, sphingolipids have emerged as important bioactive molecules in the regulation of microbial pathogenesis. Previously we reported that the sphingolipid pathway gene, ISC1, which is responsible for ceramide production, is a major virulence factor in Cn infection. Here we report our studies of the role of ISC1 during genotoxic stress induced by the antineoplastic hydroxyurea (HU) and methyl methanesulfonate (MMS), which affect DNA replication and genome integrity. We observed that Cn cells lacking ISC1 are highly sensitive to HU and MMS in a rich culture medium. HU affected cell division of Cn cells lacking the ISC1 gene, resulting in cell clusters. Cn ISC1, when expressed in a Saccharomyces cerevisiae (Sc) strain lacking its own ISC1 gene, restored HU resistance. In macrophage-like cells, although HU affected the proliferation of wild type (WT) Cn cells by 50% at the concentration tested, HU completely inhibited Cn isc1Δ cell proliferation. Interestingly, our preliminary data show that mice infected with WT or Cn isc1Δ cells and subsequently treated with HU had longer lifespans than untreated, infected control mice. Our work suggests that the sphingolipid pathway gene, ISC1, is a likely target for combination therapy with traditional drugs such as HU.